ROLE OF PERCEIVED VALUE ON CUSTOMER LOYALTY THROUGH OPTIMIZATION OF SERVICE QUALITY AND INNOVATION - Husin, Husin; Hermawati, Adya; Purbaningsih, Yuli; Susriyanti, Susriyanti; Fettry, Sylvia; Ali, Shujahat (Universitas Brawijaya, Indonesia, 2023)
Service providers must pay attention to customer satisfaction in their activities. They must focus on the quality of services provided and the need for innovation to increase customer value. It is important because service providers often pay little attention to the customer's perceived value in supporting service quality. The quantitative approach is used in this research. Data analysis is statistical and involves hypothesis tests. The survey is also conducted in which the data are obtained through a questionnaire. The object of research is service quality, innovation, perceived value, and customer loyalty. The research population is the customers of BPR Kedung Jaya Surabaya, with a sample of 100 respondents. The data collection instrument involves a questionnaire, documentation, and observation. The measurement scale is Likert Scale. The analysis technique in this research is a descriptive statistic and partial least square assisted by Smart PLS software. Results of the study show that: service quality has a significant effect on perceived value, innovation has a significant effect on perceived value, service quality has a significant effect on customer loyalty, innovation has a significant effect on customer loyalty, perceived value has a significant effect on customer loyalty, service quality significantly affects customer loyalty with the mediation of perceived value, and innovation significantly affects customer loyalty with the mediation of perceived value. This research implies that BPR Kedung Jaya Surabaya can use the results of this research as guidance to strengthen customer loyalty by examining all factors that influence research variables.